The Effect of Washing and Fermentation of Cassava Peel on the Concentration of HCN and Rumen VFA Production - Suranindyah, Yuni (2012)
The experiment was conducted to investigate the effect of treatments on cassava peel on hydrogen cyanide (HCN) content and rumen VFA production. Two varieties of cassava (white and red peel) were used in the experiment. Cassava peel were processed by chopping in 2 cm x 2 cm then were divide into 2 treatments. The treatments consisted of washing and yeast fermentation for 48 hours. After treatment cassava peel were exposed in the sun for drying so that formed chips. The result of analysis indicated that varieties of cassava did not affect HCN content. The concentration ranged from 513 to 958 mg/kg. Processing cassava peel by washing and fermentation reduced the concentration of HCN from 878.70 mg/kg to 97.59 mg/kg and 36.29 mg/kg. Fresh cassava peel produced 67.71 m mol/liter rumen volatile fatty acid (VFA), while those processed by washing and fermenting produced 65.77m mol and 76.98 m mol/liter. The study concluded that processing cassava peel reduced HCN concentration but fermentation was more effective to attain non toxic level. Rumen VFA production did not attain the optimum concentration to support microbial growth.